Syringomyelia Presenting As Obstructive Sleep Aponea - Terence E McManus; Carole A Cooke; John Wilson; Ken F Whyte (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
The authors describe a case of syringomyelia associated with Chiari malformation Type I in a patient who was referred to a respiratory service with features of obstructive sleep apnoea. The patient exhibited clinical features of scoliosis, hoarseness, sensory and motor neurological deficit and vertical upbeat jerk nystagmus. The authors review the various factors in the pathogenesis of this unusual constellation of symptoms, signs and radiological findings